Impact of Intervention on Healthcare Waste Management in a Reference Laboratory - Qasim, Javeria; Maria Mushtaq Gill; Irfan Ali Mirza; Riaz, Muhammad Omair; Sakeenah Hussain Naqvi; Sajjad, Rabia (Pakistan Armed Forces medical journal, 2025)
Objective: To assess the effect of interventions on knowledge and practices of healthcare staff regarding healthcare waste management, in the department of Microbiology, Armed Forces Institute of Pathology, Rawalpindi. Study Design: Quasi-experimental study Place and Duration of study: Department of Microbiology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from July-December 2022 Methodology: This study was conducted over 33 participants including laboratory technologists, sanitary workers and Medical laboratory technology (MLT) students. The baseline knowledge and practices were checked by using an “Awareness questionnaire” and an “Observation checklist” respectively. Interventions included lectures, posters and on-spot checks. The same questionnaires were used to assess the post-intervention knowledge and practices. The pre-and post-intervention awareness scores were compared using and a p-value of <0.05 was considered statistically significant. Results: Out of total 33 participants, 22(67%) were males and 11(33%) were females. An improvement in the knowledge and practices of the participants was noted. The improvement in knowledge between the pre and post-intervention awareness scores was found to be statistically significant with a p-value of <0.001. The on-spot practices assessed through an observation checklist revealed that pre-intervention percentage scores ranged from 38-83% while the post-intervention percentage scores ranged from 83-100%, in the nine sub-sections of the Microbiology Department. Conclusion: The three interventions, including training, display of posters and spot checks resulted in a statistically significant improvement in the awareness and marked improvement in practices of most of the laboratory staff regarding implementation of waste management policy Keywords: Healthcare, Intervention, Knowledge, Practice, Training, Waste management.